Unlocking the Power of Peer Assessment Technique: A Catalyst for Enhanced Writing Skills in Higher Education - Citra Ayu; Ramanda Rizky (STAI Hubbulwathan Duri, 2023)
The Peer Assessment Technique provides an opportunity for individuals to evaluate each other, and encourages lifelong learning and continuous improvement. Moreover, this current study aims to investigate the impact and influence of the Peer Assessment Technique on students' writing skills. Besides, the first-year students in the odd semester of 2023/2024 who attended the writing class were selected as the research sample using the simple random sampling technique. The Peer Assessment Technique was used as a treatment in the experimental class. Then, the scores from the students' post-test were analyzed using the Mann-Whitney test to see the significance between the two classes. As a result, the data analysis showed that the Z score was negative (-4.161.) which indicated that an alternate hypothesis (Ha) was accepted, and the null hypothesis (H0) was definitely rejected. At the same time, the Peer Assessment Technique is considered to have a notable for its impacts on promoting students' writing skills since it has promoted a more efficient and quality-oriented learning environment.